2018
DOI: 10.3390/cancers10060167
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Importance of Epstein–Barr Virus-Associated Gastric Cancer

Abstract: Epstein–Barr virus-associated gastric carcinoma (EBVaGC) is the most common malignancy caused by EBV infection. EBVaGC has definite histological characteristics similar to gastric carcinoma with lymphoid stroma. Clinically, EBVaGC has a significantly low frequency of lymph node metastasis compared with EBV-negative gastric cancer, resulting in a better prognosis. The Cancer Genome Atlas of gastric adenocarcinomas proposed a molecular classification divided into four molecular subtypes: (1) EBVaGC; (2) microsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 89 publications
2
57
0
3
Order By: Relevance
“…1,17,18 Arikawa et al and Nishikawa et al reported that EBVGC is derived from chronically inflamed gastric mucosa resulting from Helicobacter pylori (HP) infection. 19,20 Characteristics and typical endoscopic images of EBVGC are shown in Table 1 and in Figure 2, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1,17,18 Arikawa et al and Nishikawa et al reported that EBVGC is derived from chronically inflamed gastric mucosa resulting from Helicobacter pylori (HP) infection. 19,20 Characteristics and typical endoscopic images of EBVGC are shown in Table 1 and in Figure 2, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the causal association between the infection with Epstein Barr virus (EBV) and GC has been well documented, and it is now considered that about 10% of cases of GC are due to this viral infection [29]. EBV is known for its oncogenic properties related to its interference with cell cycle, and has been causally associated with several other cancers.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Profiling of these mediators of immune response may enable non‐invasive diagnosis of EBV status when tumor tissue is unavailable. Immune checkpoint blockade has transformed the treatment paradigms for many cancers and is a promising new treatment option for EBV‐positive GC . Few studies in patients with advanced or recurrent GC have reported a benefit from immunotherapy, and clinical trials evaluating the impact of checkpoint inhibitors in patients with EBV‐positive tumors are underway.…”
Section: Microbial Agents In Gastric Cancermentioning
confidence: 99%